1995
DOI: 10.1098/rspb.1995.0195
|View full text |Cite
|
Sign up to set email alerts
|

Bird orientation: displacement experiments with young autumn migrating wheatears,Oenanthe oenanthe, along the Arctic coast of Russia

Abstract: M igratory naive birds are thought to find the m igration route from their natal site to a specific w intering area by either clock-and-com pass orientation or goal area navigation. These two alternative hypotheses were tested by extensive longitudinal displacem ents of juvenile w heatears, hatched in northeastern Siberia, on their first au tu m n m igration tow ards the w intering area in East Africa. O rientation of individual birds was repeatedly recorded in circular orientation cages, under n atu ral clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 17 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…An alternative consideration would be that the geographic direction obtained from the star compass is a complementary mechanism used in combination with another compass such as, for example, the magnetoclinic route outlined above, where an additional cue should provide the westerly or easterly direction. However, the stars are almost impossible to see during the polar summer, so they are likely used only later in the season at high latitudes or predominantly at lower latitudes (see also above; Åkesson et al 1995, 2001a, 2005). Finally, the magnetic loxodrome is the least successful mechanism performing badly in numerousness cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative consideration would be that the geographic direction obtained from the star compass is a complementary mechanism used in combination with another compass such as, for example, the magnetoclinic route outlined above, where an additional cue should provide the westerly or easterly direction. However, the stars are almost impossible to see during the polar summer, so they are likely used only later in the season at high latitudes or predominantly at lower latitudes (see also above; Åkesson et al 1995, 2001a, 2005). Finally, the magnetic loxodrome is the least successful mechanism performing badly in numerousness cases.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the simulations included here were performed in the northern hemisphere, where the magnetic compass may be challenging to use due to the steepness of the geomagnetic field lines (Wiltschko and Wiltschko 1972). Experimental data from studies performed with wild birds in the field, however, suggest that birds have the capacity to use the natural geomagnetic field to find meaningful migration directions also in the high Arctic (Sandberg et al 1998; Åkesson et al 1995, 2001a, 2005; Muheim et al 2006), including waders (Gudmundsson and Sandberg 2000; Grönroos et al 2010). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not known for certain whether birds can use their magnetic compass under such extreme conditions (cf. Sandberg et al 1991Ðkesson et al 1995), although indications of proper orientation without access to celestial cues have been demonstrated for snow buntings (Plectrophenax nivalis) in cage experiments at a site 400 km from the magnetic North Pole, with an inclination angle of 898 .…”
Section: (C) Magnetic Loxodromesmentioning
confidence: 98%
“…The results of the orientation experiments under clear versus overcast skies conducted on a flat rooftop during spring migration with Palaearctic nocturnal migrant European Robins, Erithacus rubecula, demonstrated that birds oriented significantly under both clear and overcast skies in a seasonally meaningful migratory direction [57]. The orientation funnel experiments clearly demonstrate the ability of birds to perform orientation without an approach to celestial cues [58][59][60][61][62][63]. They appear to have the ability to determine a compass route utilizing magnetic cues.…”
Section: Discussionmentioning
confidence: 90%